Budget performance and socioeconomic development in a district municipality of the Huanuco region, Peru - Calero, Roberto (2023)
Objective. To determine the relationship between budget performance and socioeconomic development in the district of Santa María del Valle, Huanuco region, period 2012-2022. Methods. The research was characterized as applied, with a descriptive-correlational level and a non-experimental design. The theoretical framework used was public management focused on the efficiency of the execution of public spending allocated to relevant sectors in the development of society. Results. A positive relationship was found between budget performance and socioeconomic development (0.61) of the district. Likewise, a positive relationship was found between the dimensions of budget execution in the health and sanitation sectors with access to health services (0.53) or drinking water and drainage (0.71), respectively. Meanwhile, for budget execution in the education sector and the level of illiteracy, a negative relationship was found (-0.49). Conclusions. Based on the results, it can be affirmed that better municipal budget performance focused on relevant sectors, such as health, sanitation and education, is related to an increase in the level of socioeconomic development of the population (higher levels of access to health services, drinking water and sewage, or a lower level of illiteracy).